IMPLEMENTASI TECHNOLOGY ACCEPTANCE MODEL (TAM) DAN INFORMATION SYSTEMS SUCCESS MODEL (ISSM) DALAM MENGUKUR EFEKTIFITAS PENGGUNAAN SISTEM INFORMASI SIKADUKU UNIVERSITAS KUNINGAN: STUDI KASUS PENGGUNA SIKADUKU DI LINGKUNGAN UNIVERSITAS KUNINGAN - Rio Priantama (Cloud Information, 2018)
Integrated Academic Information System of Kuningan University (SIKADUKU) is an integrated academic information system built and developed in Kuningan University as a strategic step in organizational management. UNIKU as an organization needs to pay attention to the existence of factors that can influence effectiveness of the use of Information System so that the occurrence of "productivity paradox", can be minimized for that need to do empirical test about factors influencing individual user in using information system and its effect to system effectiveness so the value of benefits can be achieved as expected. This study was made with the aim to know the factors that influence the effectiveness of the use of information systems SIKADUKU in the University of Kuningan. This study will discuss the effectiveness measured by using the factor of user satisfaction. According to stakeholders’ point of view, effectiveness is a consideration of the benefits gained by users over the use of information systems (Seddon et al., 2000 in Widowati Achjari, 2004). Then, the factors that can affect users’ satisfaction are system quality, information quality, service quality, while individual users give influential factors that is belief of the power of Web system (web self- efficacy), personal innovativeness and attitude towards the portal. The research method used is quantitative by using Questionnaire instrument, then it is analyzed by using Linear Regression with SPSS 21 software assisted. Keywords: Academic Information System, Technology Acceptance Model, IS Success Model, User Satisfaction, Single Benefit